Identifikasi Senyawa Volatil dan Non-volatil Flavor Cabuk (Bungkil Wijen, Sesamum indicum Terfermentasi) - , Helmi Ajinugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cabuk is fermented food from sesame cakes that has savory taste and distinctive strong aroma.This is potentially developed as seasoning. However, some of people didnât like this strong aroma. Therefore, this study was aimed to identify some non-volatile compounds like free amino acids, nucleotide and volatile compounds that were affecting taste, and umami, and aroma of cabuk, respectively. Cabuk was made from sesame cakes, by product of roasted sesame oil extraction. Spontaneous fermentation of sesame cake were done for 60 hours in semi-aerob. The non-volatile compounds, including dissolved sugars, organic acids, free amino acids and 5'-nucleotides were identified using high pressure liquid chromatography (HPLC). While volatile compounds of cabuk were prepared by headspace solid-phase micro extraction (HS-SPME) method and were identified by aroma extract dilution analysis (AEDA) method using gas chromatography-mass spectrofotometry olfactometry (GC-MSO). The results showed that non-volatile compounds which potential to flavor of cabuk were malic acid, succinic and propionic acid providing sour sensation and free amino acids histidine, alanine, methionine, valine, phenyl alanine which was affecting the taste of sweet/ bitter/ sulfur. Aspartate, glutamate and some of nucleotides were GMP and AMP, provide savory or umami taste sensations. Intensity of umami taste was calculated by equivalent umami concentration (EUC). EUC values of cabuk reach 36.92 g/100g MSG or equal to 0.3692 MSG. Dimethyl trisulfide and 3-methyl-butanoic acid were the main volatile compounds involved in aroma of cabuk. Based on these results, it can be concluded that cabuk was potentially developed as a seasoning.